The Impact of Atmospheric Circulation on Air Temperature Rise in Estonia - Lakson, Merily; Post, Piia; Sepp, Mait (Frontiers in Earth Science, 2019)
In comparison to the global average, the climate in the Baltic Sea region, including in Estonia, has warmed particularly fast. From synoptic climatology’s point of view, a question can be posed: is this warming caused by changes in the frequency of particular circulation types or has warmer weather started accompanying these types? The main aim of the present study is to analyze the relationship between the increase of air temperature and changes in atmospheric circulation during the period of 1966–2015. Changes in the frequency of circulation types belonging to 12 classifications from the COST733 data set and changes in accompanying air temperature were analyzed. The circulation types were divided into “warm” and “cold” for a given season according to daily temperature anomalies in three Estonian meteorological stations. On the basis of the similar air flow direction, circulation types from different classifications were selected for inter-comparison. Linear trend analysis showed that there were only a few statistically significant (p < 0.05) changes in the frequency of circulation types. The major changes occurred in spring – the frequency of eastern and northeastern flow types decreased, and the frequency of types related to northwestern flow increased. However, the positive temperature anomalies increased for practically all circulation types. Particularly strong warming has taken place in winter “cold” types. In conclusion, the increase of Estonian air temperature during the analyzed period is more likely associated with the changes of temperature within circulation types than of their frequency.